2015
DOI: 10.1021/acs.biochem.5b00894
|View full text |Cite
|
Sign up to set email alerts
|

LXR Agonism Upregulates the Macrophage ABCA1/Syntrophin Protein Complex That Can Bind ApoA-I and Stabilized ABCA1 Protein, but Complex Loss Does Not Inhibit Lipid Efflux

Abstract: Macrophage ABCA1 effluxes lipid and has anti-inflammatory activity. The syntrophins, which are cytoplasmic PDZ protein scaffolding factors, can bind ABCA1 and modulate its activity. However, many or “much” of the data assessing the function of the ABCA1–syntrophin interaction are based on overexpression in nonmacrophage cells. To assess endogenous complex function in macrophages, we derived immortalized macrophages from Abca1+/+ and Abca1−/− mice and show their phenotype recapitulates primary macrophages. Abca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This investigation showed that sntb1 is induced (more than 5-fold increase) in pIC-treated salmon MLCs at 24 HPS. SNTB1 is documented to modulate mammalian macrophage lipid efflux [ 127 ], but its function in antiviral responses is not well-understood. The qPCR assays showed a slight up-regulation for optn in pIC-exposed salmon MLCs (1.5-fold); this was, however, a lower fold-change than that seen in the microarray results.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation showed that sntb1 is induced (more than 5-fold increase) in pIC-treated salmon MLCs at 24 HPS. SNTB1 is documented to modulate mammalian macrophage lipid efflux [ 127 ], but its function in antiviral responses is not well-understood. The qPCR assays showed a slight up-regulation for optn in pIC-exposed salmon MLCs (1.5-fold); this was, however, a lower fold-change than that seen in the microarray results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of LXR suppresses angiogenesis through induction of ApoD [ 47 ]. Activation of LXR leads to an increased expression of Abca1 [ 22 ] and Abcg1, proteins important for cholesterol efflux from cells [ 48 ]. In relation to inflammation, Ito et al showed that LXR inhibits NF-kB and MAPK signaling by disrupting membrane lipid organization through Abca1.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages have multiple pathways by which these cholesterol efflux pumps can be induced. This includes the induction of ABCA1 transcription by LXR following apoptotic cell uptake ( 103 ). In parallel, signaling through the efferocytic receptor BAI1 induces a signaling through the BAI1/ELMO/Rac1 pathway that leads to upregulation of ABCA1 in an LXR-independent manner ( 104 ).…”
Section: Efferocyte Metabolismmentioning
confidence: 99%
“…In parallel, signaling through the efferocytic receptor BAI1 induces a signaling through the BAI1/ELMO/Rac1 pathway that leads to upregulation of ABCA1 in an LXR-independent manner ( 104 ). Both the LXR-dependent and -independent pathways enable macrophages to export excess cholesterol absorbed during efferocytosis, thus maintaining cholesterol homeostasis within the cell and avoiding death of the efferocyte ( 103 , 104 ). The consequences of impaired cholesterol efflux can be dire.…”
Section: Efferocyte Metabolismmentioning
confidence: 99%